Pengaruh Profitability, Leverage Dan Growth Terhadap Nilai Perusahaan LQ-45 BEI Periode 2016-2018 - Adi Calvin Limanjaya, Hendang Tanusdjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This study aims to examine the effect of profitability, Leverage, and growth on firm value in companies listed on the Indonesia Stock Exchange (IDX) LQ-45 index in the 2016-2018 period. Sampling techniques using purposive sampling method. Data is processed using Spss Statistics 25.This study uses 31 companies within 3 years period and the result using 93 unit sampling. The results of this study indicate that profitability and Leverage significantly influence firm value, while growth does not have any effect on the firm value.